(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of the study is to research the serum TWEAK levels in obstructive sleep apnea syndrome (OSAS) patients.Material and Methods: Eighty-six subjects were admitted in the study, 59 being in the patient group and 27 in the control group. The patient group was further divided into subgroups of severe OSAS and mild-moderate OSAS. TWEAK levels between the groups were statistically compared. In addition, the correlation of sleep-related variables with TWEAK levels was investigated in the patient group.Results: TWEAK levels were lower in the patient group than in the control group. When the correlation between TWEAK levels and sleep-related variables are examined, inversely correlation between TWEAK levels and apnea-hypopnea index, the percentage of total sleep time spent with oxygen saturation below 90% and oxygen desaturation index was found.Conclusion: Serum TWEAK levels in OSAS patients and its relation with sleep variables showed for the first time that TWEAK may be a new inflammatory biomarker for OSAS.